The Relationship Between Added Sugar Consumption Patterns and the Risk of Obesity Among Urban Secondary School Adolescents in Indonesia - Erlingga, Syilviani (Indonesian Health Journal, 2025)
This study examines the relationship between added sugar consumption patterns and the risk of obesity among urban secondary school adolescents in Indonesia. The research employed a quantitative, cross-sectional design, using a food frequency questionnaire (FFQ) and anthropometric measurements to collect data from 400 adolescents aged 12-17 years. The results revealed a high prevalence of sugary drink and snack consumption, with over 75% of participants consuming sugar-sweetened beverages at least three times a week. The study found a positive correlation between frequent sugar consumption and higher BMI values, with adolescents consuming more than 30 grams of added sugar per day being significantly more likely to be classified as overweight or obese. Socioeconomic factors played a crucial role, as lower-income adolescents consumed more sugar compared to their higher-income peers. The findings highlight the need for targeted public health interventions to reduce sugar intake and promote healthier dietary habits, particularly among lower-income urban adolescents. Schools and policymakers are encouraged to implement strategies that limit sugary food and drink availability while promoting physical activity.